Hide ‘n seek: individual behavioural responses of cattle excreting different amounts of nematode eggs—potential threshold for pasture contamination assessment - Guzhva, Oleksiy; Hessle, Anna; Högberg, Niclas; Lidfors, Lena; Höglund, Johan (Frontiers in Animal Science, 2024)
The aim of this study was to investigate how the activity of cattle under natural grazing conditions is related to their individual parasite contribution (IPC). Potentially, the individuals contributing most to the contamination of the pasture with gastrointestinal nematodes (GIN) could then be identified and selectively treated based on sensor data thresholds. A total of 58 steers of the dairy breeds Swedish Red (SR, n=19) and Swedish Holstein (SH, n=39) were used for sensor-based data collection which lasted for a total of 10 weeks from 4 May to 13 July 2023. All steers were inoculated with a priming dose of nematode larvae and weighed in conjunction with the pasture release. The animals were then divided into four experimental groups and treated with ivermectin (IVM PO, Boehringer Ingelheim, 0.5 mg/kg BW) at different intervals to obtain an exposure contrast (Group A -was left Untreated, Group B/IVM PO-4w -treated after four weeks, Group C/IVM PO-8w -treated after eight weeks and Group D/IVM PO-4&8w -treated after four and then eight weeks. The steers were tweighed on four further occasions, during which faecal samples were also taken for parasite testing. Activity data was collected using leg-mounted IceQube sensors and body weight data and faecal samples were collected bi-weekly. The new threshold metric (IPC) was proposed for individuals with different FEC levels (NO <20 EPG, LO = 20-150, ME = 150-250 EPG and HI = >250 EPG). The effects of IPC on activity patterns were analysed stepwise using a Generalised Estimating Equations model implemented in Python programming language. Results showed significant effects of different IPC values on motion index and number of steps taken (adjusted p-value of .008, .018, .041 and .001 for individuals with NO, LO and ME IPC values, respectively). There were some breed effects on the average number of steps and minutes spent lying. The results also provide alternative threshold methods aimed at finding more sustainable ways of using anthelmintics and integrating individual data into future parasite control strategies.